Identification and analysis of barriers for harnessing geothermal energy in India. (March 2022) - Puppala, Harish; K Jha, Shibani; Singh, Ajit Pratap; Madurai Elavarasan, Rajvikram; Elia Campana, Pietro
Abstract: The Indian Government envisaged generating 10 GW using geothermal power by 2030. Reaching this milestone is linked with numerous challenges, as geothermal exploitation in India is in the nascent stages. In this work, possible barrier categories and barriers to harness geothermal energy in India are identified with the help of literature review and questionnaire-based surveys. Fuzzy Delphi method is used to find the significant barriers among the listed. Subsequently, Fuzzy Analytical Hierarchy Process (Fuzzy AHP) is used to determine the relative dominance of each barrier category and the barriers within each category. Outcomes of this research show that the resource barrier category obtained highest priority. This category includes various barriers such as (i) conceptualization of geothermal reservoir, (ii) estimation of theoretical heat energy, (iii) determination of extractable power, and (iv) selection of suitable extraction schemes. Results suggest that a comprehensive conceptual model presenting the subsurface variation of thermo-hydro-geological parameters with depth at a geothermal field can support the accurate depiction of the available and extractable thermal potential. Stability of the obtained hierarchy is examined by sensitivity analysis. Findings of this study help to identify the barriers that can be reasonably encountered and to propose developmental activities to harness geothermal energy. Highlights: An overview of the geothermal exploration works in India is discussed. Barrier categories and barriers to harness geothermal energy in India are identified. Fuzzy Delphi Analysis shows that 19 out of 28 identified barriers are pertinent. The resource barrier category obtained the highest priority. Developmental works that help to overcome the existing barriers are proposed.